The foreign service and American public opinion dynamics and prospects - Pollard, Michael S.; Ries, Charles P. 1951-; Amiri, Sohaela (Rand Corporation, 2022)
In May 2020, the authors fielded a series of questions on attitudes about recruitment, priorities, and challenges affecting American diplomats to a nationally representative, probability-based sample of 2,026 Americans ages 24 and older. Respondents were participants in RAND's American Life Panel (ALP). In June 2021, the authors re-surveyed 1,829 of the same panel participants asking the same questions, with some wording modifications. Between the two ALP surveys, RAND researchers led 14 online focus groups to ask 118 representative Americans more-detailed questions about the reasons for their views on American diplomacy and diplomats. Focus group members were not taken from the ALP and were balanced by gender, demographic category, education, and region. The authors found generally favorable public opinion attitudes toward American diplomats but also found limited understanding of what diplomats do, how they are selected, and how diplomacy interacts with other elements of America's national security establishment. Survey respondents and focus group participants considered support for American citizens abroad to be a core-and much valued-function for diplomats. Survey respondents and focus group participants were less aware that diplomats abroad have export promotion and business support responsibilities. The authors found worrisome levels of opinion that American diplomats, while trustworthy, were politically biased. The finding that the American public had greater confidence in career ambassadors than political appointees also implies that the public would support reduced politicization of State Department positions. Finally, there was a clear preference for diplomats to lead in foreign policy, as opposed to military leaders
Keywords: Diplomatischer Dienst; Öffentliche Meinung; Außenwirkung; USA; United States / Foreign Service / Employees; Diplomatic and consular service, American / Public opinion